IMMUNOLOGICAL DETECTION OF DESTRUCTIVE CHANGES IN ORGANS AND EVALUATION OF DEPENDENCE ON INDICATORS OF INTESTINAL DYSBIOSIS (World Bulletin of Public Health, 2024)
Qualitative and quantitative indicators of the local intestinal microbiota and bacteria of the facultative group were studied using the classical bacteriological method. The susceptibility of tissues to degradation in the study was determined immunologically using quantitative indicators of antigenbinding lymphocytes. Representatives of the intestinal microbiota analyzed the statistical correlation between changes in quantitative indicators and the frequency of antigen-binding lymphocytes
Keywords: students; intestinal dysbiosis; tissue antigen